Forensic digest: the discourse on heinous crimes in Mindanao Court of Appeals - Rafal, Grace S. (UPT Bahasa Universitas Tanjungpura, 2021)
This study investigated the discourse of the Court of Appeals (CA) in Mindanao, Philippines. It examined the court decisions reversely decided in the Fiscal Year 2013 on heinous crimes filed in the Court of Appeals. This research focused on the different rhetorical and discursive devices employed in the court decisions and examined how these devices performed in the production of the text to grant the appellant’s request on the reversal of the decision in the case. It scrutinized the ideological themes in the reversed decisions through the lenses of Critical Discourse Analysis and Rhetorical Analysis. The different rhetorical devices employed in the court decisions are organized into preeminent rhetorical devices, or devices most often used in the court decisions, and peripheral rhetorical devices, or those minimally used. The Preeminent Rhetorical Devices are double speak, slanting, ambiguity, aphorism, repetition, subordinate clause / delayed sentence, periodic sentence, passivization, and active voice. The Peripheral Rhetorical Devices are weaselers, aporia, and hypophora. The discursive devices employed in the production of the Court Decisions are scene-setting, specificity /indirect quotes, blame, consensus/ collaboration, pre-modifiers, extreme case formulations, and disclaimers. The ideological themes manifested in the specimens are the power asymmetry and just to cast the blame by the victim or the family of the victim and by the law enforcers. under power asymmetry are unsound judgment among trial or lower courts, abuse of power by the trial or lower court and by the law enforcers or arresting officers, and poor as victims of injustices. The following generated postulates are: pre-arranged signal: a non-verbal forensic discourse; Rule on chain of custody: the mantra of the drug crime discourse; Extrajudicial oral confessions discourse; and The charge and solve discourse.